Higher Acceptance of Videotelephonic Counseling Formats in Psychosomatic Medicine in Times of the COVID-19 Pandemic - Lohmiller, Jacqueline; Schäffeler, Norbert; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2021)
Background Due to the COVID-19 pandemic, the healthcare system in general and psychosomatics in particular were forced to change counseling-specific services and break up established structures. At the beginning of 2020, telephone as well as videotelephonic counseling options had to be quickly established. Methods Patients (n=278) of the psychosomatic medicine and psychotherapy were asked to complete a specially designed questionnaire to assess the acceptance of the counseling format following each counseling session in the period between July 2020 and February 2021. Results Satisfaction and acceptance of the three counseling formats (office, telephone, video) were rated (1-6) on average as "good" to "very good" in the three subgroups (1.5±0.9). Likewise, the "therapeutic relationship" scored high in all three subgroups in terms of establishing a strong therapeutic relationship (4.4±1.5). "Hurdles" were rated as low and tolerable (1.8±1.3). The global assessment of therapeutic contact was significantly better in the video group compared to telephone and office consultation (p<0.05). Predictor analyses showed that there was an influence of age, but not gender, on the acceptance of digital counseling formats in the present sample (F(1, 277)=4.50, p=0.04). Discussion & Conclusion Digital consultation formats were perceived by patients as promising addition to the classic face-to-face setting. Digital formats (telephone, video) were not generally preferred to face-to-face counseling, but especially video counseling was accepted and perceived with great satisfaction and acceptance. Accordingly, the additional use of digital counseling formats, especially video telephony, could be an opportunity to enrich the existing structures also after the pandemic.